2012
DOI: 10.1002/bit.24724
|View full text |Cite
|
Sign up to set email alerts
|

Anion exchange membrane adsorbers for flow‐through polishing steps: Part II. Virus, host cell protein, DNA clearance, and antibody recovery

Abstract: Anion exchange membrane adsorbers are used for contaminant removal in flow-through polishing steps in the manufacture of biopharmaceuticals. This contribution describes the clearance of minute virus of mice, DNA, and host cell proteins by three commercially available anion-exchange membranes: Sartobind Q, Mustang Q, and ChromaSorb. The Sartobind Q and Mustang Q products contain quaternary amine ligands; whereas, ChromaSorb contains primary amine based ligands. Performance was evaluated over a range of solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 15 publications
4
39
0
Order By: Relevance
“…Of the possible membrane adsorber moieties available, AEX membrane adsorbers are already known to efficiently clear mammalian viruses (Miesegaes et al, ; Phillips et al, ) across wide pH ranges (Strauss et al, ), and viral pIs (Miesegaes et al, , ; Valera et al, ). However, technological gaps have been identified as some buffer conditions required for a lower pI monoclonal antibody product can reduce clearance efficiency when product is present (Weaver et al, ,). For CP, AEX membrane adsorbers are the most attractive/cost‐effective resin for continuous flow‐through operation, since they can easily be exchanged when they are clogged.…”
Section: Viral Clearancementioning
confidence: 99%
“…Of the possible membrane adsorber moieties available, AEX membrane adsorbers are already known to efficiently clear mammalian viruses (Miesegaes et al, ; Phillips et al, ) across wide pH ranges (Strauss et al, ), and viral pIs (Miesegaes et al, , ; Valera et al, ). However, technological gaps have been identified as some buffer conditions required for a lower pI monoclonal antibody product can reduce clearance efficiency when product is present (Weaver et al, ,). For CP, AEX membrane adsorbers are the most attractive/cost‐effective resin for continuous flow‐through operation, since they can easily be exchanged when they are clogged.…”
Section: Viral Clearancementioning
confidence: 99%
“…Chromatography and chromatofocusing are of special interest for large-scale production (Okada et al, 2009), since empty and full particles can be separated by chromatography, as shown for AAV (Qu et al, 2007). The use of membrane absorbers to capture the protoparvovirus MVM has also been described recently (Weaver et al, 2013).…”
Section: Efficient Purification and Concentration Of H-1pv Preparationsmentioning
confidence: 99%
“…AEX membranes have become widely utilized in the industry due to their high load capacities, greater flow rates, reduced processing time, disposability, and lower buffer consumption . Several authors have demonstrated robust membrane‐based clearance at neutral pH and low salt buffer conditions . Resin‐based AEX columns are also effective and can be reused dozens of times, as long as proper cleaning and regeneration procedures are followed, but have the disadvantage of increased operational complexity.…”
Section: Scientific and Technology Considerationsmentioning
confidence: 99%